Kontekstualisasi Fikih Melalui Prinsip Kemaslahatan - Ansori Ansori (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
The existence of Islamic law (fiqh) wich is able to improve the society condition and to solve many problems is such a fact. Contextualize needs to be done continuously and one of the guidance is goodness principal.